Developing English Book for X TKR of Vocational High School Based on Contextual Purposes: English - Ita Nurhasanah; Istina Atul Makrifah; Tyas Alhim Mubarok (Journal of English Development, 2024)
This research aims to develop an English book for X TKR of Vocational High School by implementing an Independent curriculum. Base on the result of need analysis with students and interviews with English teacher, the researchers find the problem that SMK Darul Huda Blitar implementing independent curriculum but do not have patent materials for learning English using the independent curriculum. The product was created using the R&D approach with five stages of ADDIE model: analysis, design, development, implementation, and evaluation. In this study, the research instruments and data sources were from need analysis questionnaire, interview guidelines, and student satisfaction questionnaire. The results of research show that English learning books accompanied by illustrations, a little material and equipped with practice can increase understanding and enthusiasm in lessons. Based on the results of a student satisfaction questionnaire filled out by 19 students after using English books for contextual purposes, the score reached 96%, which means this media is very good for use in increasing interest and understanding in English lessons.